Studi Viabilitas Benih Kedelai (Glycine Max [L.] Merril.) Varietas Dega-1 Pada Berbagai Proporsi Kapur Tohor Dalam Dua Ukuran Wadah Pascasimpan Empat Bulan - Ermawati, Ermawati (Jurnal Agricultural Biosystem Engineering, 2025)
Soybean seeds are classified as orthodox seeds with high protein content, which makes them susceptible to quality deterioration during storage. Therefore, proper storage methods are required to maintain seed viability until the next planting season. This study aimed to (1) determine the optimum proportion of calcium oxide to maintain soybean seed viability during storage, (2) evaluate the effect of storage container size on seed viability, and (3) examine the interaction between calcium oxide proportion and container size on seed viability. The research was conducted at the Seed and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung, from July to November 2021. The experiment used a factorial randomized complete block design (5 × 2) with three replications, resulting in 30 experimental units. The first factor was the proportion of calcium oxide (0.0%, 7.5%, 15.0%, 22.5%, and 30.0%), while the second factor was storage container size (3 L and 5 L). Data were analyzed using Bartlett’s test, Tukey’s test, and orthogonal comparisons at a 5% significance level. The results showed that different proportions of calcium oxide did not significantly affect seed viability. Similarly, storage container size had no significant effect. Overall, soybean seeds maintained high viability after four months of storage, indicated by high germination percentage (91.29%), maximum growth potential (98.44%), and seedling vigor, along with low moisture content (7.45%) and electrical conductivity. No interaction was observed between calcium oxide proportion and storage container size.